Adolescents' Perceptions of Communication with Parents About Sexuality - Borualogo, Ihsana Sabriani; Hatta, Muhammad Ilmi; Khasanah, Andhita Nurul; Mubarak, Ali (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
This study aimed to explore the topics adolescents discuss with their parents, how frequently these conversations occur, and how important adolescents perceive them to be. The participants were 331 middle school students aged 12–16 years (53.8% girls, 46.2% boys), selected through convenience sampling. Data were gathered using a questionnaire covering four domains of sexual communication: developmental and social issues, sexual safety, sexual experiences, and sexual activities. We applied Friedman test on data from a related sample, the Wilcoxon signed-rank test, the Mann-Whitney U test for comparing independent groups, and Spearman rank correlation. Results revealed that communication patterns differ between mothers and fathers. Mothers were more likely to discuss developmental and social issues, while fathers more often addressed sexual experiences. The findings highlight the need to enhance parent-adolescent communication about sexual matters.